PERILAKU MENYIMPANG REMAJA DESA SUNGAI ALANG KECAMATAN KARANG INTAN KABUPATEN BANJAR KALIMANTAN SELATAN - Muhammad Ihsan (Prodi PPKn ULM dan AP3KnI Kal-Sel, 2014)
Muhammad Ihsan, 2014. Teenage deviant behaviour village sub-district Karang Intan Reed Creek district of Banjar in South Kalimantan. Program Study of Citizenship and Pancasila Education, Department of Social Scienes Education,Faculty of Teacher and Education Science, University of Lambung Mangkurat. Supervising (1) Zainul Akhyar (2) H. Harpani Matnuh During this adolescent behavior of the village of Sungai Alang tend to have yet to achieve good behavior as expected. It is seen from the actions and behaviour of the teenagers are shown to still be in the Act of perversion. Research objectives are to find out other forms of deviant behavior of teenagers in the village of Sungai Alang,to determine the factors that led to the teen deviant behaviour in the village of Sungai Alang, to find out the attitude of the community towards deviant behavior of teenagers.The data source is composed of primary data and secondary data. Data collection techniques used are observation, interview and documentation. The results of this research indicate the forms of juvenile delinquency can be seen by the presence of symptoms, drinking alcohol, etc, the factors causing occurrence of juvenile delinquency internal factors and external factors, the right attitude to cope with teenage deviant behaviour is preventive action, the repressive measures, and rehabilitative and curative actionSuggestions in this study are for adolescents to behave so as not to stray again, for the community in order to better monitor and control the actions of teenagers, for the local government as input, for the researchers as experience, for parents to be able to be a good role model, for community leaders as a description of the behavior of teenagers of the village.